Comparison of Adaptation and Microleakage of CAD/CAM Restorations to Inlay Cavities Prepared by Using Different Finishing Methods - Ayben Şentürk; Mehmet Ali Kılıçarslan; Merve Çakırbay Tanış; Mert Ocak; İbrahim Berk Bellaz (European Annals of Dental Sciences)

(untitled)
Purpose: To compare the adaptation and microleakage of CAD/CAM inlay restorations using conventional or ultrasonic finishing equipment and their combinations.Materials & Methods: Inlay cavities were prepared on 66 extracted human lower first molar teeth using one of the following finishing methods: Group I: straight fissure diamond bur; Group II: fissure diamond bur and ultrasonic tip; Group III: 6º tapered conical diamond bur; Group IV: 6º tapered conical diamond bur and ultrasonic tip. Inlay restorations milled from feldspathic ceramic blocks were cemented with resin cement. Adaptation and microleakage of the restorations were evaluated by micro-CT. The adaptation of the restorations was evaluated in four areas and five determined points. The differences between the finishing methods were statistically evaluated at each measurement point.Results: The adaptation of the restorations differed between 1.07 and 330.71 µm. Statistical differences were observed in the marginal and internal adaptation of ceramic inlay restorations due to the finishing method used at some points of the ceramic and cavity interface. However, the microleakage values between the finishing methods did not show a statistical difference.Conclusion: According to the results of this study, the microleakage of the ceramic inlay restorations is not affected by the finishing method used. However, the adaptation of the restoration could be affected by the finishing method, depending on the area.Clinical Significance: Preparations for inlay restorations prepared with these special burrs and ultrasonic instruments created better marginal fit, which could result in more successful ceramic inlays.